Book Review: STEFAN TH. GRIES, “STATISTICS FOR LINGUISTICS WITH R: A PRACTICAL INTRODUCTION”. BERLIN/ BOSTON: MOUTON DE GRUYTER, 2021, 495 P. - Nicoleta MANLUP (Studia Universitatis Babeş-Bolyai. Philologia, 2022)
Having two previously published editions (2009 and 2013), the current edition (2021), Statistics for Linguistics with R: A Practical Introduction, revises and brings into discussion an updated part of the quantitative analysis methods adapted to linguistics and widely presented in their earlier versions. In order to shed light on the importance of statistics in linguistics, the author, Stefan Th. Gries, puts together some important background information that should be acquired by anyone interested in a quantitative type of research in the field of linguistics and languages. The author himself mentions that this particular book is different from other introductions in statistics because ‘it has been written especially for linguists’ (p. 1).